Zoomorphic Penannular Brooches - Kilbride-Jones, H.E (Reports of the Research Committee of the Society of Antiquaries of London, 1980)
This is a study of a distinctive type of Celtic jewellery called zoomorphic penannular brooches, popular in the British Isles from the second century AD to the mid fifth century AD. In this type of jewellery, the terminals are fashioned into stylised animals' heads. The brooches are fully illustrated, and their find-spot, description, present location and publication reference are given.